60 Years of CERN Experiments and Discoveries - Luigi Di Lella (Advanced Series on Directions in High Energy Physics, 2015)
The book is a compilation of the most important experimental results achieved during the past 60 years at CERN - from the mid-1950s to the latest discovery of the Higgs particle. Covering the results from the early accelerators at CERN to those most recent at the LHC, the contents provide an excellent review of the achievements of this outstanding laboratory. Not only presented is the impressive scientific progress achieved during the past six decades, but also demonstrated is the special way in which successful international collaboration exists at CERN. Contents: Foreword (R-D Heuer) Preface (L Di Lella and H Schopper) The Discovery of the Higgs Boson at the LHC (P Jenni and T S Virdee) Precision Physics with Heavy-Flavoured Hadrons (P Koppenburg and V Vagnoni) Toward the Limits of Matter: Ultra-relativistic Nuclear Collisions at CERN (J Schukraft and R Stock) The Measurement of the Number of Light Neutrino Species at LEP (S Mele) Precision Experiments at LEP (W de Boer) The Discovery of the W and Z Particles (L Di Lella and C Rubbia) The Discovery of Weak Neutral Currents (D Haidt) Highlights from High Energy Neutrino Experiments at CERN (W-D Schlatter) The Discovery of Direct CP Violation (L Iconomidou-Fayard and D Fournier) Measurements of Discrete Symmetries in the Neutral Kaon System with the CPLEAR (PS195) Experiment (T Ruf) An ISR Discovery: The Rise of the Proton-Proton Cross-Section (U Amaldi) Deep Inelastic Scattering with the SPS Muon Beam (G K Mallot and R Voss) Revealing Partons in Hadrons: From the ISR to the SPS Collider (P Darriulat and L Di Lella) Properties of Antiprotons and Antihydrogen, and the Study of Exotic Atoms (M Doser) Muon g-2 and Tests of Relativity (F J M Farley) The Discoveries of Rare Pion Decays at the CERN Synchrocyclotron (G Fidecaro) Highlights at ISOLDE (K Blaum, M J G Borge, B Jonson and P Van Duppen) Readership: Graduate students and researchers in elementary particle physics, and historians of science.